Late Payment Penalty: Ta’widh And Gharamah Imposed To Debtor From The Shariah Perspective - Zuhaira Nadiah Binti Zulkipli (Yuridika, 2019)
Islamic financial institutions had face problems and barriers such as the problem of delayed financing settlement (for any reason), where it is not possible to impose any interest due to the delay or the cessation of settlement which practiced in conventional banks due to riba’ prohibited (haram) in Shariah principles. This situation is more detrimental when some customers who purposely delay payment of their debts or purposely refuse to pay due to the absence of rules concerning penalty for late payment in Islamic banks. As a result, the Islamic banks had fail to achieve their targeted profits when the problem of debt payment occurs, the Islamic banks have to bear all the losses and finally face difficulties in achieving sustainability and lose out in their efforts to compete with the conventional banks which accept time-based interest for every default late payments of debts. This study aims to discuss the permissibility of late payment charges by way of ta’widh and gharamah from the Shariah perspective and to find the applicable law in Malaysia. Besides, the implementation of ta’widh and gharamah can be described as in the resolutions of the Shariah Advisory Council of Bank Negara Malaysia (SAC). Further, it will elaborate on how related this late payment charges with the concepts of Shariah, Maqasid of Shariah and Maslahah according to judgement of the fundamentals of the Islamic Jurispendence. Lastly, it will also discuss on how the imposition of ta’widh and gharamah is different from riba for deferred debts in Islamic financial institutions.